Principles and practices of Critical Thinking Models in language development (International Journal of Food and Nutritional Sciences, 2019)
This abstract explores the application of critical thinking models in enhancing English language abilities. Models such as Bloom's Taxonomy, the Paul-Elder Critical Thinking Framework, and the Socratic Questioning Approach offer structured approaches to intellectual engagement, enabling learners to go beyond rote memorization. By integrating these models, language students can develop analytical skills, evaluate information critically, and express ideas with clarity and precision. The Paul-Elder Framework, emphasizing intellectual traits, guides learners to question assumptions, contributing to refined language use. Socratic questioning encourages active dialogue, fostering nuanced language expression. Bloom's Taxonomy serves as a roadmap for progressing from basic language skills to higher-order thinking. These models collectively provide a comprehensive framework for language development, empowering learners with the cognitive tools necessary for effective communication and a deeper understanding of the English language